From the Basic Psychological Needs Satisfaction to Intrinsic Motivation: Mediating Effect of Academic Integration - Vergara-Morales, Jorge; Del Valle, Milenko (Frontiers in Psychology, 2021)
The studies show a positive and direct relationship between basic psychological needs satisfaction and intrinsic motivation of the students. However, there is a lack of studies that analyze the psychological processes that affect these relationships. For this reason, the purpose of this study was to investigate the mediating role of academic integration on the relationship between basic psychological needs satisfaction and intrinsic motivation of Chilean university students. The participants were a total of 580 students from a university in northern Chile, 359 women and 221 men. The mediation analysis was performed by structural equations modeling, using the maximum likelihood method and the bootstrapping procedure with 10,000 iterations. The results indicated that academic integration fully mediated the relationship between basic psychological needs satisfaction and intrinsic motivation of the students. Therefore, the basic psychological needs satisfaction had an indirect effect on the intrinsic motivation of the students through the academic integration. It is concluded that academic integration constitutes a psychological process that promotes the development of intrinsic motivation for learning. The practical implications are discussed along with the limitations of the study and recommendations for future research.